Progress of laser cooling of 12C3+ ions at the CSRe. (July 2015) - Wang, H B; Ma, X; Wen, W Q; Huang, Z K; Zhang, D C; Hai, B; Zhu, X L; Zhao, D M; Li, J; Ma, X M; Yan, T L; Mao, R S; et al.
Synopsis: We have performed a test run for laser cooling experiments with 12 C 3+ ion beams at an energy of 122 MeV/u at the CSRe with a pulsed laser. During this beamtime a lot of progress have been made. This was the first time we could successfully separate the 12 C 3+ ions and 16 O 4+ ions in the Schottky spectrum with the help of electron cooling. And our newly installed CPM detector worked well during the experiment. We tried to see effects from the interaction of the pulsed laser light with the stored 12 C 3+ ion beams, but no cooling effects could yet be observed.